320 ONTOGENY OF GLUCOCORTICOID RECEPTOR EXPRESSION IN THE NEONATAL RAT BRAIN. (1st January 2005) - Lee, B. H.; Wen, T. C.; Rogido, M.; Genetta, T.; Sola, A.
Abstract : Background: Glucocorticoids play a key role in multiple cellular processes, including immune function, inflammation, and cell death. Its effects are mediated by the glucocorticoid receptor (GR), predominantly expressed in the cortex and hippocampus of the adult brain. We have previously shown that GR expression is downregulated in the cerebral cortex of the neonatal rat in response to focal cerebral ischemia; however, little is known about the ontogeny of GR expression in the neonatal brain. Objectives: To elucidate the ontogeny of GR expression in the neonatal rat brain. Methods: For Western blot analysis, Sprague-Dawley rat pups were sacrificed on postnatal day 1 (P1), P3, P7, or P10 (n = 4 per time point) and homogenates were obtained from the cortex, striatum, and cerebellum. Digital densitometry was used to quantitate Western blot results. For immunohistochemistry (IHC), pups were perfused with 4% paraformaldehyde in 0.1 M phosphate buffer (pH 7.4) on P1, P3, P7, or P10 (n = 4 per time point) and serial frozen sections (40 μm thick) were obtained from harvested brains. Western blots and IHC were based on an anti-rabbit GR antibody with AP anti-rabbit IgG labeling and NBT-BCIP band visualization for Western blots and biotinylated anti-rabbit IgG labeling with peroxidase-conjugated streptavidin and cobalt-glucose oxidase-DAB intensification visualization for IHC. Results: Compared to the cortex, GR expression by Western blot was 16% greater in the hippocampus, 28% greater in the striatum, and 6% greater in the cerebellum. However, this pattern altered with increasing postnatal age, with steady increases in cortical levels, maintenance of hippocampal levels, fluctuation of striatal levels, and marked decreases in cerebellar levels. By P10, compared to analogous regions at P1, GR expression was 12% greater in the cortex, 3% lower in the hippocampus, 1% lower in the striatum, and 28% lower in the cerebellum. Immunohistochemistry staining confirmed the Western blot findings. Conclusions: To our knowledge, this is the first report of GR ontogeny in the developing neonatal rat brain. All areas of the neonatal brain expressed GR at birth. During the first 10 days of life, cortical GR expression steadily increased while that in the cerebellum steadily decreased; GR expression in the hippocampus and striatum remained relatively constant during this time. GR mRNA determinations from the cortex during P1 to P10 are ongoing. Understanding the ontogeny of GR expression in the neonatal rat brain will aid with interpretation of alternations in GR expression in response to insults or medications used in this neonatal animal model.